Cathedral at Durham
At Durham, as at Ely, the structure alternates between circular and compound piers. The rhythm is, however, quite different, and only the compound piers, with their attached shafts, were designed to support the high vault. The aisles were vaulted on a square plan obtained by the insertion of the major planning square. Something of the problems involved in the use of rib vaulting with semicircular ribs a square plan can be seen in the way the diagonal ribs arrive at the column capital at a different angle to that of the cross ribs. This was to give cause for concern whilst building the high vault. The aisles, which were largely complete by 1096, have the earliest ribbed vaults in England. Previously, vaulting was of uniform thickness and the parts of the vault met at a simple junction, or groin. Groined vaulting was largely superceded by the rib supports a thinner arched infill.